Predicting student academic achievement based on different types of mindsets among college students - Mohd Shahabuddin, Khairul Najlah; Ali, Nornabilah; Zhang, Ying; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
A common and maladaptive opinion is that only smart people can succeed with high CGPA. The purpose of this study was to determine the mindset status of bachelor level students in Universiti Putra Malaysia (UPM) and to investigate the differences between the types of mindset on gender, household income, parents' education level and CGPA. This study used questionnaires which adopted from Dweck, C.S. (2006) to measure fixed and growth mindsets to look at their associations to gender, SES, CGPA and also parents education levels of college students. The results suggested that there is a significant difference between the growth mindset in regard to gender, household income, parent's education level and CGPA. However, for the fixed mindset, the expected result seems to be contradicted as only parent’s education level has a significant difference whereas the other variables do not bear any significance.